FONDEN--Mexico’s National Disaster Fund : An Evolving Inter-Institutional Fund for Post-Disaster Expenditures - World Bank (Washington, DC, 2015)
Fund for Natural Disasters (FONDEN) is a financial vehicle that ensures the GoM has adequate financial capacity following natural disasters. FONDEN builds on its inter-institutional framework, requiring collaboration between federal ministries and affected State governments. FONDEN continues to evolve, leveraging its resources with innovative market-based risk transfer instruments to increase funding in extreme loss years.